Fieldwork of the Canadian Institute in Greece in 2016 - Rupp, David W.; Bonias, Zizis; Perreault, Jacques Y.; Charami, Alexandra; Burke, Brendan; Burns, Bryan; Carter, Tristan; Athanasoulis, Dimitris; Nakassis, Dimitri; Gallimore, Scott; James, Sarah; Karapanou, Sophia; et al. (Mouseion: Journal of the Classical Association of Canada, 2019)
The archaeological fieldwork conducted in Greece in 2016 under the aegis of the Canadian Institute in Greece is summarized here based on the presentation given by the Director at the Institute's annual Open Meeting in Athens, in May, 2017.